The Optimization of Cream Body Scrub with Black Rice Extract and Aloe Vera Extract - Nailufa, Yuyun Nailufa, (Universitas Muhammadiyah Gresik, 2024)
Black sticky rice has a fairly high antioxidant. Black Sticky Rice Contains Vitamin B1, magnesium, iron and protein. It is can help maintain skin health and make skin look brighter. Aloe vera extract contains saponins contained in aloe vera gel can clean dirt from the skin. In addition, aloe vera also contains vitamin E which can potentially moisturize the skin. This study aims to designing formulas body scrub with herb black sticky rice and aloe vera extract and observe physical characteristics and physical stability for 3 months. Physical characteristic evalusion includes homogeneity test, organoleptis test, pH test, dispersion test and viscosity test. The stability test was carried out for 3 months of storage at room temperature and 40°C. The results showed that body scrub cream with black sticky rice and aloe vera extract on F2 was the most optimal formula and stable during storage of 90 days or 3 months.